2014
DOI: 10.1111/josi.12082
|View full text |Cite
|
Sign up to set email alerts
|

Do You Say Something When It's Your Boss? The Role of Perpetrator Power in Prejudice Confrontation

Abstract: Two experiments examined the role of perpetrator power in witnesses’ decision to confront a prejudicial remark. In Experiment 1, participants who witnessed a sexist remark by a higher‐power (vs. an equal‐power) perpetrator were significantly less likely to express confrontation intentions, despite finding the remark highly biased and inappropriate. In Experiment 2, participants read scenarios involving a sexist versus racist remark perpetrated by someone higher vs. lower vs. equal in power, and they reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 35 publications
0
68
0
Order By: Relevance
“…Indeed, confronting prejudice can both empower confronters and discourage perpetrators through increased negative affect and guilt (Czopp, Monteith, & Mark, 2006). However, extant research has found that this confrontation does not always occur in workplace scenarios due to the ambiguity of subtly discriminatory comments (Jones, Peddie, et al, 2016) or hesitation to take on the responsibility of confronting a perpetrator (Ashburn-Nardo, Blanchar, Petersson, Morris, & Goodwin, 2014;Ashburn-Nardo, Morris, & Goodwin, 2008). Furthermore, in some instances, confrontation may even be discouraged due to the fact that bystanders do not wish to be victimized themselves (Porath & Erez, 2009).…”
Section: Bystander Experience Of Subtle Discriminationmentioning
confidence: 99%
“…Indeed, confronting prejudice can both empower confronters and discourage perpetrators through increased negative affect and guilt (Czopp, Monteith, & Mark, 2006). However, extant research has found that this confrontation does not always occur in workplace scenarios due to the ambiguity of subtly discriminatory comments (Jones, Peddie, et al, 2016) or hesitation to take on the responsibility of confronting a perpetrator (Ashburn-Nardo, Blanchar, Petersson, Morris, & Goodwin, 2014;Ashburn-Nardo, Morris, & Goodwin, 2008). Furthermore, in some instances, confrontation may even be discouraged due to the fact that bystanders do not wish to be victimized themselves (Porath & Erez, 2009).…”
Section: Bystander Experience Of Subtle Discriminationmentioning
confidence: 99%
“…Reciprocal anger and complementary fear reactions are the most common responses to someone's anger expression (Dimberg, Thunberg, & Elmehed, 2000;Lelieveld et al, 2012;Van Kleef et al, 2004). Thus the perceived effectiveness of the anger expression depends on the ratio between the anticipated desired and undesired outcomes (Ashburn-Nardo, Blanchar, Petersson, Morris, & Goodwin, 2014;Good, Moss-Racusin, & Sanchez, 2012). For example, the perpetrator's fear reactions may lead to compliance with the expresser's demands, whereas angry reactions may fuel a desire to retaliate (Lelieveld et al, 2012;Van Kleef & Côt e, 2007).…”
Section: Studymentioning
confidence: 99%
“…For example, men could be taught about existing barriers that prevent both women and men from confronting sexism (Shelton & Stewart, ; Swim & Hyers, ; Woodzicka & LaFrance, ). Special emphasis should be placed on the power of situational barriers in which a power‐discrepancy might further inhibit women from confronting sexism (Ashburn‐Nardo, Blanchar, Petersson, Morris & Goodwin, ), as these are the situations in which allies might be most vital in the fight against sexism. This lesson should decrease the likelihood that men will interpret a lack of confrontational behavior by women as a sign that sexism did not occur, and if it did, that it was not harmful.…”
Section: Increasing Men's Sensitivity To Sexismmentioning
confidence: 99%